PROFESSIONALISM AS AMANAH: THE ROLE OF ACADEMIC ORGANIZATIONS IN ENHANCING LECTURER COMPETENCE IN ISLAMIC HIGHER EDUCATION - Sita Ratnaningsih; Yazid Hady; Afrizal Abdul Hafizh (Nurul Jadid University, Paiton Probolinggo, East Java, 2025)
This study aims to analyze how professional organizations contribute to the transformation of lecturer capacity development in PTKIN, examine their contribution to the implementation of the tridharma of higher education, and identify the challenges and opportunities they face. The study employed a mixed-methods design conducted from June to October 2024, involving lecturers from several PTKIN affiliated with PD-PGMI and PPMPI. Data were collected through in-depth interviews, questionnaire surveys, and document analysis. Qualitative data were analyzed thematically, while quantitative data were processed using descriptive statistics and integrated at the interpretation stage. The findings show that professional organizations function as academic platforms for professional learning, knowledge exchange, collaboration, publication support, and networking. Participation in these organizations strengthens teaching, research, publication, and broader academic engagement. However, their transformative role is constrained by limited funding, uneven participation, organizational capacity issues, and insufficient institutional support. This study concludes that professional organizations should be recognized as transformative academic infrastructures that connect individual lecturer development with broader institutional advancement in PTKIN.